Composite material with interlaminar toughening particles and method of making same
By using chemically active thermoset particles in fiber-reinforced polymer composites, the shortcomings of the composite in post-impact compression strength and fracture toughness are solved, and higher damage tolerance and fracture toughness are achieved, reducing crack propagation and microcracks.
Patent Information
- Application Number
- CN202411723972.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2017-11-08
- Filing Date
- 2018-11-07
- Publication Date
- 2025-03-04
AI Technical Summary
Existing fiber-reinforced polymer composites have shortcomings in post-impact compression strength and fracture toughness, especially in the crack propagation and microcrack problems in the interlayer area.
Chemically active thermosetting particles are used as interlayer toughening particles, and covalent bonds are formed by reacting with the thermosetable resin matrix to improve the damage tolerance and fracture toughness of the composite material.
The compression strength and fracture toughness of the composite material are significantly improved, crack propagation and microcracks in the interlayer areas are reduced, and the material is debonded and microcrack resistance is enhanced.
Smart Images

Figure CN119550705A_ABST
Abstract
Description
This application is a divisional application of the following application: Application date: November 7, 2018; Application number: 2018800858269; Invention name: "Composite material with interlayer toughening particles and method for manufacturing the same". Technical Field
[0001] The present disclosure generally relates to fiber reinforced polymer (FRP) composites having toughening particles therein, and a method of making such composites. BRIEF DESCRIPTION OF THE DRAWINGS
[0002] Figure 1 Shown is a scanning electron microscope (SEM) image of ground thermosetting particles prepared according to one example.
[0003] Figure 2 A cross-sectional view of the cured composite laminate is shown, where distinct interlaminar regions can be seen. DETAILED DESCRIPTION
[0004] Fiber reinforced polymer (FRP) composites have been used as high-strength, low-weight engineering materials to replace metals in aerospace structures (such as the primary structure of aircraft). Important properties of such composites are high strength, high stiffness and reduced weight.
[0005] Multiple layers of prepreg plies are commonly used to form structural composite parts with a laminated structure. Delamination of such composite parts is an important failure mode. Delamination occurs when two layers become debonded from one another. Important design constraints include both the energy required to initiate delamination and the energy required to propagate delamination.
[0006] A cured composite material (e.g., a prepreg layup) having improved delamination resistance is a composite material having improved compressive impact strength (CAI) and fracture toughness (G Ic and G IIc ) composite materials.
[0007] CAI measures the ability of a composite material to withstand damage. In a test to measure CAI, the composite material is subjected to an impact of a given energy and then loaded under compression. The damage area and indentation depth are measured after the impact and before the compression test. During this test, the composite is restrained to ensure that no buckling instabilities occur and the strength of the composite is recorded.
[0008] Fracture toughness is a property that describes the ability of a material containing a crack to resist breaking, and is one of the most important properties of materials used in aerospace applications. Fracture toughness is a quantitative way of expressing a material's resistance to brittle fracture when a crack is present.
[0009] Fracture toughness can be quantified as the strain energy release rate (G c), which is the energy dissipated per unit of newly created fracture surface area during fracture. G c Including G IC (Mode 1-Open Mode) or G IIC (Mode II - in-plane shear). The subscript "IC" indicates a Mode I crack opening formed under a normal tensile stress perpendicular to the crack, and the subscript "IIC" indicates a Mode II crack generated by a shear stress acting parallel to the crack plane and perpendicular to the crack front. The initiation and growth of delamination is typically determined by examining the Mode I and Mode II fracture toughnesses.
[0010] The CAI performance of fiber-reinforced polymer composites can be improved by two main techniques. The first technique involves the use of high-strength reinforcing fibers with relatively high failure strains. These fibers appear to absorb a large amount of energy without breaking, thereby redistributing the energy over a larger area of the composite laminate.
[0011] CAI properties and interlaminar toughness (G IC and G IIC ) can be improved by incorporating certain toughening particles in the interlayer region of a multilayer composite laminate. "Interlayer region" refers to the region between two adjacent layers of reinforcing fiber structure in a composite laminate. The presence of toughening particles in the composite laminate creates a resin-rich interlayer, which helps inhibit crack propagation in this interlayer region.
[0012] Conventionally, thermoplastic particles such as polyamide (PA) have been incorporated into the interlayer region of composite laminates to improve CAI. "Interlayer region" refers to the region between adjacent reinforcing fiber layers in a multilayer composite laminate. However, thermoplastic particles based on polyamides may have a low melting point (Tm), especially those with long aliphatic chains, or have too high hygroscopicity, such as those with short aliphatic chains. Amorphous thermoplastic particles such as amorphous PA or PI may have poor solvent resistance. Another commonly encountered problem is that due to the mismatch of the coefficient of thermal expansion (CTE) between the particles and the surrounding resin matrix, a poor interface is generated between the thermoplastic particles and the thermosetting matrix in which these particles are embedded. This CTE mismatch can cause debonding during thermal cycling testing. This is commonly referred to as microcracking and is a major problem in the aerospace industry.
[0013] The present disclosure relates to the use of chemically active or "active" thermosetting particles as interlaminar toughening particles for improving the damage tolerance and fracture toughness of fiber reinforced polymer composites. More specifically, these particles contain chemical functional groups that can react with a heat-curable resin matrix, and these chemical functional groups are dispersed in the heat-curable resin matrix to form covalent bonds during the curing of the resin matrix.
[0014] In one embodiment, the chemically active particles are obtained by partially curing a heat curable resin composition beyond its gel point to obtain "solid-like" properties, followed by grinding to obtain the desired particle size. Due to the partial curing, there are unreacted or uncrosslinked functional groups on the surface of the particles. These particles are sufficiently crosslinked beyond the gel point of the resin composition to maintain the integrity of the particles when curing the composite laminate in which the particles are embedded and to ensure the formation of distinct interlaminar regions.
[0015] In another embodiment, the thermosetting resin composition is formulated so that the ratio of one or more thermosetting resins to one or more curing agents in the curable resin composition is adjusted so that the composition contains a non-stoichiometric ratio of one or more thermosetting resins and one or more curing agents, i.e., the amount of one or more curing agents required to react with 100% of the one or more thermosetting resins is insufficient or excessive, and therefore, due to this deficiency or excess, at the end of the entire curing cycle, there will be unreacted or uncrosslinked functional groups from the thermosetting resin or curing agent. After complete curing, the cured resin is then ground to obtain particles having chemically active functional groups on the surface of the particles. In this embodiment, the resulting chemically active thermosetting particles are composed of crosslinked thermosetting resins or thermosetting polymers and chemically active functional groups capable of forming covalent bonds. When the particles are formed from a thermosetting resin composition containing one or more epoxy resins, the resulting chemically active thermosetting particles are composed of crosslinked polyepoxides and uncrosslinked functional groups.
[0016] The partially cured particles can be formed by the same or substantially the same curable resin composition, which is used to form the matrix resin of the fiber-reinforced composite material (e.g., prepreg). The term "substantially the same" means that the composition is the same as that of 50%. In one embodiment, some of the matrix resin used to form the composite material can be set aside for partial curing and grinding to form chemically active particles. The partially cured particles are then incorporated into the composite laminate at the interlaminar region. In this way, the CTE of the particles will be precisely matched to the CTE of the surrounding resin matrix, thereby eliminating stress and microcracks in the cured composite laminate. In addition, since the particles are made of the same or similar material as the matrix resin, the interface bonding between the particles and the surrounding matrix resin after curing is very strong.
[0017] It has been found that little or no CTE mismatch occurs between the "active" (chemically active) thermosetting particles and the surrounding resin matrix, and therefore the cured composite laminates exhibit improved debonding and microcracking resistance. The use of "active" thermosetting particles, as disclosed herein, differs from conventional methods used in the aerospace industry, where thermoplastic or cross-linked thermoplastic toughening particles having a different chemical nature from the surrounding matrix resin are used as interlaminar toughening particles.
[0018] The "active" thermosetting particles disclosed herein are not swellable during curing, as in the case of the crosslinked thermoplastic particles disclosed in U.S. Pat. No. 8,846,818 and U.S. Pat. No. 9,567,426. The swellable crosslinked thermoplastic particles disclosed in these patents are crosslinked, derived from a composition consisting primarily of a thermoplastic polymer, and typically do not retain reactive functional groups on the particle surface. As such, the swellable particles are not very reactive with the surrounding epoxy matrix of the composite material in which the particles are dispersed. Chemically active thermosetting particles
[0019] As used herein, the terms "cure" and "curing" include crosslinking of resin precursors or polymers produced by mixing base components, heating at elevated temperatures, exposure to ultraviolet light and radiation. As used herein, "fully cured" refers to a degree of cure of 100%. As used herein, "partially cured" refers to a degree of cure of less than 100%.
[0020] Partially cured particles are formed from a curable resin composition that has been cured to a degree of cure of less than 100%, such as a full cure in the range of 50%-99%, including 55%-95%, 50%-86%, 50%-87%, 50%-88%, 50%-89%, 55%-86%, 60%-86%. The curable resin composition contains one or more thermosetting resins, at least one curing agent, and optional additives such as thermoplastic polymers, elastomeric materials, conductive particles, organic fillers, etc. At a degree of cure of 50% or more, the thermomechanical properties of the material are significantly altered and the material has "solid-like" properties.
[0021] To form partially cured particles, thermal curing is performed beyond the gel point of the resin composition. This gel point can be defined as the intersection between the G' and G" curves derived from rheological analysis during the cure cycle. G' represents the elastic modulus and G" represents the viscous modulus.
[0022] The degree of cure of a thermosetting resin system can be determined by differential scanning calorimetry (DSC). Thermosetting resin systems undergo irreversible chemical reactions during cure. As the components in the resin system cure, the resin releases heat, which is monitored by the DSC instrument. The heat of cure can be used to determine the percent cure of the resin material. For example, the following simple calculation can provide this information: % cure = [ΔH 未固化的 -ΔH 固化的 ] / [ΔH 未固化的 ]X 100%
[0023] As an example, when the particles are formed from a heat-curable resin composition containing one or more epoxy resins and an amine compound as a curing agent, the resulting chemically active thermoset particles are composed of crosslinked polyepoxides, uncrosslinked epoxy functional groups, and unreacted amine groups.
[0024] In alternative embodiments, the ratio of one or more thermosetting resins to one or more curing agents in the curable resin composition is adjusted so that the composition contains an insufficient or excessive amount of one or more curing agents required to react with 100% of the one or more thermosetting resins, and therefore, due to this insufficient or excessive amount, at the end of the predetermined curing cycle, there will be unreacted or uncrosslinked functional groups from the thermosetting resin material. For example, if X amount of curing agent is required to achieve a 100% degree of cure in a predetermined curing cycle, less than X amount of curing agent can be used in the resin composition to achieve chemically active particles, such as up to 90% X, including 50%-80% X or 60%-70%. Alternatively, if X amount of curing agent is required to achieve a 100% degree of cure in a predetermined curing cycle, greater than X amount of curing agent can be used in the resin composition to obtain chemically active particles, such as at least 110% X, including 120%-150% X or 130%-140%.
[0025] To determine the lowest possible amount of curing agent (i.e., hardener) within a useful range, the simplified Carothers equation described in Robert J. Young, Peter A. Lovell, Introduction to Polymers, Third Edition, pp. 46-47 (CRC Press, June 27, 2011) can be used. For a given epoxy resin or other thermosetting resin with a functionality (e.g., 2, 3, 4, etc.), when reacted with a curing agent with a given functionality (e.g., 2, 3, 4, etc.), the simplified Carothers equation is a method of predicting the amount of conversion (extent of reaction) required to reach the gel point. The relationship of the gel point to the functionality available for crosslinking is defined as n = 2 / 2-pf, where n = the number average degree of polymerization, p = the decimal range of reaction, where 1 represents 100% reaction, and f = the total number of functional groups that undergo the crosslinking reaction. The equation typically defines the gel point when n = infinity. For a trifunctional epoxy resin and a difunctional hardener, when p = 0.4 or 40% conversion, the total functionality is 5, so n = infinity. For a tetrafunctional epoxy resin and a tetrafunctional hardener (e.g., a diprimary amine), f = 8 and gelation is predicted to occur at 25% conversion, etc.
[0026] When the resin composition is fully cured, the cured material contains unreacted / uncrosslinked functional groups, which are the source of chemically active functional groups capable of forming covalent bonds. For example, when an epoxy resin and an amine curing agent are used and the amine compound is insufficient, the resulting cured particles contain unreacted / uncrosslinked epoxy functional groups. Conversely, when the amine compound is excessive, the resulting cured particles contain unreacted amine groups.
[0027] As an example, when the particles are formed from a heat-curable resin composition containing one or more epoxy resins and an amine compound as a curing agent, and when the amine compound is present in an insufficient amount, due to an excess of the one or more epoxy resins, the resulting chemically active thermosetting particles are composed of crosslinked polyepoxide and uncrosslinked epoxy functional groups.
[0028] The chemically active particles may have an average particle size (d50) of less than about 100 μm, e.g., 10-70 μm, 15-50 μm, or 15-30 μm, or 20-25 μm. As disclosed herein, the average particle size may be measured by laser diffraction techniques, e.g., using a Malvern Mastersizer 2000 operating in the range of 0.002 nanometers to 2000 micrometers. "d50" represents the median value of a particle size distribution, or alternatively, the value of the distribution such that 50% of the particles have a particle size of that value or less.
[0029] Suitable thermosetting resins for forming the particles include, but are not limited to, epoxies, novolacs, phenolics, cyanate esters, bismaleimides, benzoxazines, polybenzoxazines, combinations thereof, and precursors thereof.
[0030] Particularly suitable are multifunctional epoxy resins (or polyepoxides) having multiple epoxide functional groups per molecule. Polyepoxides can be saturated, unsaturated, cyclic, or acyclic, aliphatic, aromatic, or heterocyclic polyepoxide compounds. Examples of suitable polyepoxides include polyglycidyl ethers prepared by the reaction of epichlorohydrin or epibromohydrin with polyphenols in the presence of a base. Thus, suitable polyphenols are, for example, resorcinol, catechol, hydroquinone, bisphenol A (bis(4-hydroxyphenyl)-2,2-propane), bisphenol F (bis(4-hydroxyphenyl)-methane), fluoro-4,4'-dihydroxybenzophenone, bisphenol Z (4,4'-cyclohexylene-bisphenol) and 1,5-hydroxynaphthalene. Other suitable polyphenols as the basis for polyglycidyl ethers are condensation products of phenol and formaldehyde or acetaldehyde of the known novolac type.
[0031] Examples of suitable epoxy resins include diglycidyl ethers of bisphenol A or bisphenol F, such as EPON available from Dow Chemical Co. TM828 (liquid epoxy resin), DER331, DER661 (solid epoxy resin); triglycidyl ethers of aminophenols, such as those from Huntsman Corp. MY 0510, MY 0500, MY 0600, MY 0610. Additional examples include phenol-based novolac epoxy resins commercially available from The Dow Chemical Company as DEN 428, DEN 431, DEN 438, DEN 439, and DEN 485; cresol-based novolac epoxy resins commercially available from Ciba-Geigy Corp. as ECN 1235, ECN 1273, and ECN 1299; hydrocarbon novolac epoxy resins commercially available from Huntsman Corporation as 71756, 556, and 756 is commercially available.
[0032] The curing agent for the curable resin composition can be selected from known curing agents, such as aromatic or aliphatic amines or guanidine derivatives. Aromatic amine curing agents are preferred, preferably aromatic amines having at least two amino groups per molecule, and diaminodiphenyl sulfone is particularly preferred, for example wherein the amino groups are in the meta or para position relative to the sulfone group. Specific examples are 3,3'- and 4,4'-diaminodiphenyl sulfone (DDS); methylene dianiline; bis(4-amino-3,5-dimethylphenyl)-1,4-diisopropylbenzene; bis(4-aminophenyl)-1,4-diisopropylbenzene; 4,4'methylenebis-(2,6-diethyl)-aniline (MDEA from Lonza); 4,4'methylenebis-(3-chloro, 2,6-diethyl)-aniline (MCDEA from Lonza); 4,4'methylenebis-(2,6-diisopropyl )-aniline (M-DIPA from Lonza Group); 3,5-diethyltoluene-2,4 / 2,6-diamine (D-ETDA80 from Lonza Group); 4,4'-methylenebis-(2-isopropyl-6-methyl)-aniline (M-MIPA from Lonza Group); 4-chlorophenyl-N,N-dimethyl-urea (e.g. Monuron); 3,4-dichlorophenyl-N,N-dimethyl-urea (e.g. DiuronTM) and dicyandiamide (e.g. Amicure TMCG 1200 from Pacific Anchor Chemical).
[0033] Suitable curing agents also include anhydrides, particularly polycarboxylic anhydrides, such as nadic anhydride, methylnadic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, endomethylenetetrahydrophthalic anhydride, and trimellitic anhydride.
[0034] To form partially cured particles, the one or more curing agents may be present in a stoichiometric amount such that there is a sufficient amount of reactive groups from the curing agent to react with the reactive groups of the one or more thermosetting resins, e.g., one (1) mole of amine curing agent per mole of epoxy resin. To form fully cured but chemically reactive particles, the stoichiometric amount is such that there is an insufficient amount of reactive groups from the curing agent to react with the reactive groups of the one or more thermosetting resins, e.g., 0.5 to 0.9 moles of amine curing agent per mole of epoxy resin. Alternatively, to form fully cured but chemically reactive particles, the stoichiometric amount is such that there is an excess of reactive groups from the curing agent to react with the reactive groups of the one or more thermosetting resins, e.g., 1.1 to 1.5 moles of amine curing agent per mole of epoxy resin.
[0035] Optional additives that can be incorporated into the curable resin composition include thermoplastic polymers, elastomers, and combinations thereof. Thermoplastic polymers can be selected from: polyamides; polyetherimides (PEI); polysulfones, including polyethersulfone (PES), polyetherethersulfone (PEES); polyphenylene oxide (PPO); poly(ethylene oxide) (PEO), phenoxy resins (thermoplastic copolymers of bisphenol A and epichlorohydrin), polyimides (PI), polyamideimides (PAI), polysulfone (Psu) ... copolymers and combinations thereof. Elastomers can be selected from: rubbers, such as amine-terminated butadiene acrylonitrile (ATBN), carboxyl-terminated butadiene acrylonitrile (CTBN), carboxyl-terminated butadiene (CTB); fluorocarbon elastomers, styrene-butadiene polymers. When present, the amount of thermoplastic polymer and / or elastomer is less than 40% by weight, for example, 5%-35% of the thermoplastic polymer based on the total weight of the resin composition, so that the particles retain their thermosetting characteristics.
[0036] Conductive materials in particulate form (e.g., particles or flakes) can also be added to curable resin compositions to impart conductivity throughout the thickness of the final composite laminate, also referred to as Z-conductivity. Examples of suitable conductive materials include metals in flake or particle form, such as silver, gold, nickel, copper, aluminum, and alloys thereof, carbon powder, nano-sized materials based on carbon, such as carbon nanotubes (single-walled carbon nanotubes or multi-walled carbon nanotubes), carbon nanofibers. As used herein, the term "nano-sized material" refers to a material having at least one size less than about 0.1 microns (<100 nanometers). Carbon nanotubes (CNTs) are tubular, strand-like structures with an outer diameter in the range of about 0.4 nm to about 100 nm (e.g., the outer diameter can be less than about 50 nm or less than about 25 nm) and an aspect ratio of up to 5000:1 from 100:1. Nanofibers can have a diameter in the range of from 70 nm to 200 nm and a length in the range of 50-200 microns. When present, the amount of conductive material is less than 10% by weight, such as 1% to 4%, based on the total weight of the resin composition.
[0037] Flame retardant additives may also be added to the curable resin composition to impart enhanced flame retardancy to the final composite laminate. For example, the Strujtol Polydis product line commercialized by Schill+Seilacher. Other commercially available flame retardants will be apparent to those skilled in the art.
[0038] In one embodiment, the particles are formed from a curable resin composition comprising: (a) one or more multifunctional epoxy resins; (b) at least one amine curing agent; and (c) a thermoplastic or elastomeric toughening agent. The amounts of components (a)-(c) may be as follows: (a) 100 parts; (b) 5 to 70 parts; (c) 5 to 50 parts.
[0039] In another embodiment, the resin composition further comprises conductive particles, such as carbon nanotubes (CNTs), carbon powder, metal particles, and combinations thereof. When present, the amount of conductive particles is up to 10% by weight based on the total weight of the resin composition, such as 1%-10%, 2%-5%.
[0040] It will be appreciated by those skilled in the art that the chemically reactive thermosetting particles of the present disclosure may be formed by other methods capable of producing such particles other than partial curing followed by grinding. Composites and Laminates
[0041] The chemically active particles disclosed herein can be used as interlaminar particles between reinforcing fiber layers of a composite laminate, ie, these particles are located in the interlaminar region of the composite laminate. "Interlaminar region" refers to the region between adjacent reinforcing fiber layers in a multi-layer composite laminate.
[0042] In some embodiments, the chemically active particles are dispersed in the interlaminar region formed between adjacent reinforcing fiber layers at a level of about 2% to about 20%, including about 5% to about 15%, and about 8% to about 12%, by weight based on the total weight of the matrix resin contained in the composite laminate.
[0043] Composite laminates containing interlayer particles can be made using different methods. In one embodiment, these particles are deposited on the surface of a plurality of prepreg plies before they are laid together to form a stack or "prepreg stack". The prepreg plies within the stack can be positioned relative to each other in a selected orientation, e.g., 0°, ±45°, 90°, etc. When the prepreg plies are stacked together to form a laminate, the particles are retained in the interlayer region of the laminate. Once in place, the prepreg stack is consolidated and cured under heat and pressure to achieve the desired fiber volume fraction and minimum voids.
[0044] The particles may be deposited onto the prepreg via any conventional technique such as spraying, electrostatic deposition, scatter coating, aerosol distribution and any other technique known to those skilled in the art. Due to the stickiness of the matrix resin, the distributed composite particles adhere to the surface of the prepreg.
[0045] In another embodiment, before this prepreg is manufactured, the particles of a specific amount are mixed with a curable resin composition. In such an embodiment, first resin film is manufactured by coating the resin mixture containing particles on release paper. Then, with the help of heat and pressure, the obtained resin film is laminated to fiber (such as unidirectional fiber) layer to impregnate fiber, thereby forming a prepreg sheet layer with specific fiber area weight and resin content. During the impregnation process, because the size of the particles is greater than the spacing between the fibers, the particles are filtered out and retained in the outside of the fiber layer. Subsequently, when two prepreg layers containing particles are laid up and down each other, these particles are located in the interlayer region of the prepreg laminate.
[0046] In an alternative embodiment, a curable resin composition without particles is applied to a release paper to form a resin film, which is then contacted with one or two opposite surfaces of an unimpregnated fiber layer. The resin impregnates the fiber and leaves a little or no resin on the outer surface of the fiber layer. Subsequently, a second film of a curable resin containing particles is contacted with the outer surface of the resin-impregnated fiber layer. An additional film of a curable resin containing particles can be contacted with the opposite outer surface of the resin-impregnated fiber layer to form a sandwich structure. As a result, a particle-rich resin layer is retained outside the impregnated fiber layer and does not further impregnate the fiber. Multiple such structures are laminated together to form a composite structure with particles in the interlayer region.
[0047] In another embodiment, two films of curable resin compositions without particles are contacted with two opposite surfaces of unimpregnated fiber layers. The resin impregnates the fibers and leaves a little or no resin on the outer surface of the fiber layer. Subsequently, two films of curable resin containing particles are contacted with the opposite surfaces of the pre-impregnated fiber layer. Multiple such structures are laminated together to form a composite structure with particles in the interlayer region. This approach is preferred because it tends to provide a well-ordered laminate produced by particles without destroying the placement of fibers.
[0048] In the embodiments disclosed herein, the term "prepreg" refers to a layer of fiber material (in the form of unidirectional fibers, nonwoven mats, or fabric layers) that has been impregnated or infused with a curable matrix resin. As used in this disclosure, the term "impregnation" refers to the introduction of a curable resin into reinforcing fibers so as to partially or completely encapsulate the fibers with the matrix resin.
[0049] The matrix resin of the prepreg may have a composition that is the same or similar to that of the chemically active particles. Likewise, the thermosetting resins, curing agents and additives previously disclosed with respect to the particles are also applicable to the matrix resin of the prepreg.
[0050] The fiber reinforcement may be in the form of a woven or non-woven fabric layer, or a unidirectional tape composed of unidirectional fibers. "Unidirectional fibers" refers to layers of reinforcing fibers that are aligned in the same direction. The prepreg plies within the stack may be positioned relative to each other in a selected orientation, e.g., 0°, ±45°, 90°, etc.
[0051] The reinforcing fibers in composite laminates and prepregs can take the form of chopped fibers, continuous fibers, filaments, tows, bundles, sheets, plies, and combinations thereof. Continuous fibers can further adopt unidirectional (aligned in one direction), multidirectional (aligned in different directions), nonwoven, weaving, knitting, stitching, winding, and braiding constructions, as well as any one of the structures of curled fiber mats, felt mats, and chopped mats. Woven fiber structures can include multiple woven tows, and each tow is made of multiple filaments (for example, thousands of filaments). In other embodiments, tows can be held in place by cross-tow stitches, weft insertion knitting stitches, or a small amount of resin adhesives (such as thermoplastic resins).
[0052] Fiber materials include, but are not limited to, glass (including electrical- or E-glass), carbon, graphite, aramid, polyamide, high modulus polyethylene (PE), polyester, poly-p-phenylene-benzoxazole (PBO), boron, quartz, basalt, ceramics, and combinations thereof.
[0053] In order to make high strength composites, such as those used in aerospace and automotive applications, it is preferred that the reinforcing fibers have a tensile strength greater than 3500 MPa (according to ASTM D4018 test method). Examples Example 1
[0054] Resin System U without toughening particles was prepared based on the formulation shown in Table 1 ("Resin U"). Table 1 Components unit Resin U Araldite MY0510 weight% 27.6 Araldite PY306 weight% 27.6 Aradur 9664-1 weight% 27.3 Sumikaexcel 5003P weight% 17.5
[0055] By adding epoxy precursor MY0510 and PY306 was mixed at a temperature ranging between 60°C and 90°C to prepare Resin U. MY0510 is triglycidyl p-aminophenol, and PY306 is a diglycidyl ether of bisphenol-F, both from Huntsman Advanced Materials Inc. Sumikaexcel 5003P (polyethersulfone from Sumitomo Chemical) was added to the epoxy mixture and then dissolved at a temperature ranging between 110°C and 130°C. Aromatic amine curing agent was then added 9664-1 (4,4'-diaminodiphenyl sulfone (4,4'-DDS) from Huntsman Advanced Materials) and mixed at a temperature ranging between 60°C and 90°C.
[0056] The resin U thus produced was then film-formed on release paper to a nominal area weight of 23.4 gsm (grams per square meter). The intermediate modulus carbon fiber was spread in a conventional prepreg machine to form a fiber web of unidirectional fibers having a nominal area weight of 190 gsm. The formed fiber web was then sandwiched between two films of resin U to obtain a prepreg U having a nominal fiber area weight (FAW) of 190 gsm and a nominal resin content of 19.8% by weight.
[0057] Four resin compositions P.1-P.4, one without particles and three containing different active thermosetting toughening particles, were prepared based on the formulations shown in Table 2. All amounts are in wt. %. Table 2
[0058] By adding epoxy precursor MY0510 and PY306 was mixed at a temperature ranging between 60°C and 90°C to prepare each resin composition in Table 2. Sumikaexcel 5003P (polyethersulfone) was added and then dissolved at a temperature ranging between 110°C and 130°C. Then, 9664-1 (4,4'-DDS) and reactive thermosetting resin particles (LRTP) and mixed at a temperature ranging between 60°C and 90°C.
[0059] Each resin composition P thus produced was then film-formed onto release paper to a nominal area weight of 23.4 gsm. Using a conventional prepreg machine, the prepreg U formed as described above was sandwiched between two resin films formed of the resin composition P containing particles to obtain a prepreg P having a nominal fiber area weight (FAW) of 190 gsm and a total nominal resin content of 33% by weight.
[0060] The different toughening particles used are labeled as VP-0X0, PK-0X0, NT-0X0 in Table 2. The three toughening particles were prepared using the resin formulations shown in Table 3. Table 3
[0061] By combining the epoxy precursor Tactix123 and PY306 was mixed at temperatures ranging between 60° C. and 90° C. to prepare resins VP-0X0, PK-0X0, NT-0X0. Tactix 123 is the diglycidyl ether of bisphenol A from Huntsman Advanced Materials.
[0062] VP-0X0 resin: then add VP3619 and 9664-1 and mixed at a temperature ranging between 70° C. and 90° C. Struktol VP3619 is a nitrile rubber modified epoxy prepolymer based on the diglycidyl ether of bisphenol A from Schielen-Selleh.
[0063] PK-0X0 resin: PKHB100 (polyhydroxy ether (ie, phenoxy resin) from InChem) was added to the epoxy mixture and then dissolved at a temperature ranging between 110° C. and 130° C. Aromatic amine curing agent Aradur 9664-1 (4,4′-DDS) was then added and mixed at a temperature ranging between 60° C. and 90° C.
[0064] NT-0X0 resin: Multi-walled carbon nanotubes were pre-dispersed in a Tactix 123 / PY306 blend. Aromatic amine curing agent Aradur 9664-1 (4,4'-DDS) was then added and mixed at a temperature ranging between 60°C and 90°C.
[0065] Three different particles (VP-0X0, PK-0X0, NT-0X0) were prepared by partially curing the three resins VP-0X0, PK-0X0, NT-0X0 by heating to 180°C at 2°C / min and cooling them immediately after reaching 180°C. The partially cured resins were granulated before grinding with an ACM classification grinder from Hosokawa. Differential scanning calorimetry (DSC) tests were performed on the initial three resins VP-0X0, PK-0X0, NT-0X0 and the three particles VP-0X0, PK-0X0, NT-0X0 made as described above, and the percentage conversion of each of the three particles was determined using the following equation: % cure = [ΔH 未固化的 -ΔH 固化的 ] / [ΔH 未固化的 ]X 100%.
[0066] The glass transition temperatures (T g ) are also obtained from these DSC tests. Finally, the particle size distribution of these particles is measured by laser diffraction using a Mastersizer 3000 from Malvern. The results are summarized in Table 4. Table 4
[0067] Figure 1 is a scanning electron microscope (SEM) image of the abrasive particles PK-0X0 disclosed in Table 4.
[0068] A plurality of prepregs P were laid up to form a composite laminate. The laminate was enclosed in a conventional zero exudate sealed vacuum bag and cured in an autoclave at 180°C at a pressure of 85 psi (586 kPa or kilopascals) for 2 hours while maintaining the vacuum throughout the cure cycle.
[0069] The cured panels were then subjected to damage resistance testing (CSAI) and microcrack testing. The results are reported in Table 5. Table 5 Resin P.1 Resin P.2 Resin P.3 Resin P.4 CSAI[ksi] 26 38.7 39.1 34.8 CSAI[MPa] 179 267 269.6 240 Particle microcracks not applicable 0 0 0
[0070] The results presented in Table 5 demonstrate the benefit of introducing these active thermoset toughening particles, improving impact properties by up to 50% without causing any particle microcracking issues.
[0071] Figure 2 A cross section of a cured composite laminate is shown where distinct interlaminar regions can be seen.
[0072] Thermal micropeeling resistance was evaluated by microscopy after 1,200 thermal cycles between -55° C. and 70° C. No microcracks were found after this test.
Claims
1. A fiber-reinforced polymer composite structure comprising: two or more layers of reinforcing fibers impregnated or infused with a curable matrix resin comprising one or more thermosetting resins and at least one curing agent; Chemically active thermosetting particles located in the interlaminar region between adjacent layers of reinforcing fibers, wherein each chemically active thermosetting particle is formed of a partially cured thermosetting polymer having a degree of cure of 50% to 86%, and each particle comprises chemically active functional groups on its surface capable of forming covalent bonds; wherein these chemically active thermosetting particles are derived from a heat-curable resin composition comprising one or more epoxy resins and at least one amine compound as a curing agent; wherein each chemically active thermosetting particle comprises a cross-linked polyepoxide, an uncross-linked epoxy functional group, and an unreacted amine group; wherein the composition of the chemically active thermosetting particles is the same or substantially the same as the composition of the curable matrix resin; The fiber-reinforced polymer composite structure is prepared by the following method, which comprises: (a) forming thermosetting particles having chemically active functional groups on the surface of the particles; (b) forming a resin film from a first curable resin composition not including the thermosetting particles; (c) forming a resin film from a second curable resin composition comprising one or more thermosetting resins, at least one curing agent, and the thermosetting particles; (d) impregnating the reinforcing fiber layer with at least one resin film formed from the first curable resin composition using heat and pressure to form a resin-impregnated reinforcing fiber layer; (e) contacting at least one resin film formed from the second curable resin composition with the surface of the resin-impregnated reinforcing fiber layer to form a particle-containing prepreg sheet layer; (f) forming an additional particle-containing prepreg ply according to steps (d) and (e); (g) laying down the prepreg plies in a stacked arrangement to form a prepreg layup; (h) consolidating the prepreg layup; and (i) curing the prepreg layup; wherein the thermosetting particles in (a) are formed by partially curing a heat-curable resin composition comprising one or more thermosetting resins and at least one curing agent to form a partially cured thermosetting resin having a degree of cure of 50% to 86%; and grinding the partially cured thermosetting resin; and Therein, during the curing of (i), the chemically active functional groups on the thermosetting particles form covalent bonds with the matrix resin surrounding the particles.
2. A fiber-reinforced polymer composite structure comprising: two or more layers of reinforcing fibers impregnated or infused with a curable matrix resin comprising one or more thermosetting resins and at least one curing agent; Chemically active thermosetting particles located in the interlaminar region between adjacent layers of reinforcing fibers, wherein each chemically active thermosetting particle is formed of a partially cured thermosetting polymer having a degree of cure of 50% to 86%, and each particle comprises chemically active functional groups on its surface capable of forming covalent bonds; wherein these chemically active thermosetting particles are derived from a heat-curable resin composition comprising one or more epoxy resins and at least one amine compound as a curing agent; wherein each chemically active thermosetting particle comprises a cross-linked polyepoxide, an uncross-linked epoxy functional group, and an unreacted amine group; wherein the composition of the chemically active thermosetting particles is the same or substantially the same as the composition of the curable matrix resin; The fiber-reinforced polymer composite structure is prepared by the following method, which comprises: (a) forming thermosetting particles having chemically active functional groups on the surface of the particles; (b) forming a plurality of prepreg plies, each prepreg ply comprising reinforcing fibers impregnated or infused with a curable matrix resin; (c) depositing the partially cured thermoset particles on at least one surface of each prepreg ply; (d) laying the prepreg plies having the particles thereon in a stacked arrangement such that the particles are located between adjacent prepreg plies to form a prepreg layup; (e) consolidating the prepreg layup; and (f) curing the prepreg layup; wherein the thermosetting particles in (a) are formed by partially curing a heat-curable resin composition comprising one or more thermosetting resins and at least one curing agent to form a partially cured thermosetting resin having a degree of cure of 50% to 86%; and grinding the partially cured thermosetting resin; and Therein, during curing of (f), the chemically active functional groups on the thermosetting particles form covalent bonds with the matrix resin surrounding the particles.
3. A fiber-reinforced polymer composite structure comprising: two or more layers of reinforcing fibers impregnated or infused with a curable matrix resin comprising one or more thermosetting resins and at least one curing agent; Chemically active thermosetting particles located in the interlaminar region between adjacent layers of reinforcing fibers, wherein each chemically active thermosetting particle is formed of a partially cured thermosetting polymer having a degree of cure of 50% to 86%, and each particle comprises chemically active functional groups on its surface capable of forming covalent bonds; wherein these chemically active thermosetting particles are derived from a heat-curable resin composition comprising one or more epoxy resins and at least one amine compound as a curing agent; wherein each chemically active thermosetting particle comprises a cross-linked polyepoxide, an uncross-linked epoxy functional group, and an unreacted amine group; wherein the composition of the chemically active thermosetting particles is the same or substantially the same as the composition of the curable matrix resin; The fiber-reinforced polymer composite structure is prepared by the following method, which comprises: (a) forming thermosetting particles having chemically active functional groups on the surface of the particles; (b) forming a curable matrix resin composition comprising one or more thermosetting resins, at least one curing agent, and the thermosetting particles; (c) impregnating a plurality of reinforcing fiber layers with the curable resin composition to form prepreg plies, each prepreg ply comprising reinforcing fibers impregnated or infused with the curable matrix resin composition and thermosetting particles retained on the outer surfaces of the layers of reinforcing fibers; (d) laying down the prepreg plies having the particles therein in a stacked arrangement to form a prepreg layup; (e) consolidating the prepreg layup; and (f) curing the prepreg layup; wherein the thermosetting particles in (a) are formed by partially curing a heat-curable resin composition comprising one or more thermosetting resins and at least one curing agent to form a partially cured thermosetting resin having a degree of cure of 50% to 86%; and grinding the partially cured thermosetting resin; and During curing of (f), the chemically active functional groups on the thermosetting particles form covalent bonds with the matrix resin surrounding the particles.
4. A fiber-reinforced polymer composite structure comprising: two or more layers of reinforcing fibers impregnated or infused with a curable matrix resin comprising one or more thermosetting resins and at least one curing agent; Chemically active thermosetting particles located in the interlaminar region between adjacent layers of reinforcing fibers, wherein each chemically active thermosetting particle comprises a cross-linked thermosetting polymer and a chemically active functional group capable of forming a covalent bond; wherein each chemically active thermosetting particle comprises a cross-linked polyepoxide and an uncross-linked epoxy functional group or an unreacted amine group; The chemically active thermosetting particles are derived from a heat-curable resin composition comprising one or more epoxy resins and at least one amine compound as a curing agent, wherein the molar ratio of epoxy groups to amine groups is such that there is a deficiency or excess of the amount of amine required to react with 100% of all epoxy groups. The fiber-reinforced polymer composite structure is prepared by the following method, which comprises: (a) forming thermosetting particles having chemically active functional groups on the surface of the particles; (b) forming a resin film from a first curable resin composition not including the thermosetting particles; (c) forming a resin film from a second curable resin composition comprising one or more thermosetting resins, at least one curing agent, and the thermosetting particles; (d) impregnating the reinforcing fiber layer with at least one resin film formed from the first curable resin composition using heat and pressure to form a resin-impregnated reinforcing fiber layer; (e) contacting at least one resin film formed from the second curable resin composition with the surface of the resin-impregnated reinforcing fiber layer to form a particle-containing prepreg sheet layer; (f) forming an additional particle-containing prepreg ply according to steps (d) and (e); (g) laying down the prepreg plies in a stacked arrangement to form a prepreg layup; (h) consolidating the prepreg layup; and (i) curing the prepreg layup; wherein the thermosetting particles in (a) are formed by: forming a heat-curable resin composition comprising one or more thermosetting resins and at least one curing agent, wherein the molar ratio of the one or more thermosetting resins to the curing agent is such that there is a deficiency or excess of the amount of amine required to react with 100% of all the epoxy resin; curing the heat-curable resin composition to form a cured resin having chemically reactive functional groups; and grinding the cured resin; and Therein, during curing of (i), the chemically active functional groups on the thermosetting particles form covalent bonds with the matrix resin surrounding the particles.
5. A fiber-reinforced polymer composite structure comprising: two or more layers of reinforcing fibers impregnated or infused with a curable matrix resin comprising one or more thermosetting resins and at least one curing agent; Chemically active thermosetting particles located in the interlaminar region between adjacent layers of reinforcing fibers, wherein each chemically active thermosetting particle comprises a cross-linked thermosetting polymer and a chemically active functional group capable of forming a covalent bond; wherein each chemically active thermosetting particle comprises a cross-linked polyepoxide and an uncross-linked epoxy functional group or an unreacted amine group; The chemically active thermosetting particles are derived from a heat-curable resin composition comprising one or more epoxy resins and at least one amine compound as a curing agent, wherein the molar ratio of epoxy groups to amine groups is such that there is a deficiency or excess of the amount of amine required to react with 100% of all epoxy groups. The fiber-reinforced polymer composite structure is prepared by the following method, which comprises: (a) forming thermosetting particles having chemically active functional groups on the surface of the particles; (b) forming a plurality of prepreg plies, each prepreg ply comprising reinforcing fibers impregnated or infused with a curable matrix resin; (c) depositing the partially cured thermoset particles on at least one surface of each prepreg ply; (d) laying the prepreg plies having the particles thereon in a stacked arrangement such that the particles are located between adjacent prepreg plies to form a prepreg layup; (e) consolidating the prepreg layup; and (f) curing the prepreg layup; wherein the thermosetting particles in (a) are formed by: forming a heat-curable resin composition comprising one or more thermosetting resins and at least one curing agent, wherein the molar ratio of the one or more thermosetting resins to the curing agent is such that there is a deficiency or excess of the amount of amine required to react with 100% of all the epoxy resin; curing the heat-curable resin composition to form a cured resin having chemically reactive functional groups; and grinding the cured resin; and Therein, during curing of (f), the chemically active functional groups on the thermosetting particles form covalent bonds with the matrix resin surrounding the particles.
6. A fiber-reinforced polymer composite structure comprising: two or more layers of reinforcing fibers impregnated or infused with a curable matrix resin comprising one or more thermosetting resins and at least one curing agent; Chemically active thermosetting particles located in the interlaminar region between adjacent layers of reinforcing fibers, wherein each chemically active thermosetting particle comprises a cross-linked thermosetting polymer and a chemically active functional group capable of forming a covalent bond; wherein each chemically active thermosetting particle comprises a cross-linked polyepoxide and an uncross-linked epoxy functional group or an unreacted amine group; The chemically active thermosetting particles are derived from a heat-curable resin composition comprising one or more epoxy resins and at least one amine compound as a curing agent, wherein the molar ratio of epoxy groups to amine groups is such that there is a deficiency or excess of the amount of amine required to react with 100% of all epoxy groups. The fiber-reinforced polymer composite structure is prepared by the following method, which comprises: (a) forming thermosetting particles having chemically active functional groups on the surface of the particles; (b) forming a curable matrix resin composition comprising one or more thermosetting resins, at least one curing agent, and the thermosetting particles; (c) impregnating a plurality of reinforcing fiber layers with the curable resin composition to form prepreg plies, each prepreg ply comprising reinforcing fibers impregnated or infused with the curable matrix resin composition and thermosetting particles retained on the outer surfaces of the layers of reinforcing fibers; (d) laying down the prepreg plies having the particles therein in a stacked arrangement to form a prepreg layup; (e) consolidating the prepreg layup; and (f) Curing the prepreg laminate wherein the thermosetting particles in (a) are formed by: forming a heat-curable resin composition comprising one or more thermosetting resins and at least one curing agent, wherein the molar ratio of the one or more thermosetting resins to the curing agent is such that there is a deficiency or excess of the amount of amine required to react with 100% of all the epoxy resin; curing the heat-curable resin composition to form a cured resin having chemically reactive functional groups; and grinding the cured resin; and Therein, during curing of (f), the chemically active functional groups on the thermosetting particles form covalent bonds with the matrix resin surrounding the particles.
Citation Information
Patent Citations
Engineered cross-linked thermoplastic particles for interlaminar toughening
US8846818B2
Engineered crosslinked thermoplastic particles for interlaminar toughening
US9567426B2
Engineered crosslinked thermoplastic particles for interlaminar toughening
CN102482398A
Fiber reinforced high modulus polymer composite with a reinforced interphase
CN104736614A
Epoxy resin composition for fiber-reinforced composite material, prepreg and fiber-reinforced composite material
JP2012188651A
Cited By
Multi-scale simulation and forward design method and system for interlaminar fracture toughness of particle toughened composite material
CN121565345A
Multi-scale simulation and forward design method and system for interlaminar fracture toughness of particle toughened composite
CN121565345B